Dominance of angular momentum exchange in the PCI recapture of photoelectrons revealed by high resolution Auger electron measurements of Kr. (12th November 2019) - Kosugi, S; Suzuki, N; Kumagai, N; Iwayama, H; Shigemasa, E; Koike, F; Azuma, Y
Abstract: An unexpectedly prominent angular momentum exchange effect in the double photoionization continuum was identified through the photoelectron recapture process induced by post-collision interaction (PCI). The Kr ( M 5 N 2, 3 N 2, 3 ) Auger electron spectrum originating from 3 d −1 5/2 photoionization was measured with the photon energy tuned very close above the ionization threshold. As the photon energy approached the 3 d −1 5/2 photoionization threshold, Rydberg series structures including several angular momentum components were formed within the Auger peak profile by the recapture of the photoelectrons into high-lying final ion orbitals. Our spectrum with line-width much narrower than the lifetime width of the corresponding core excited state allowed us to resolve detailed structures due to the orbital angular momentum states very clearly. Unexpectedly, conjugate peaks originating from the exchange of angular momentum between the photoelectron and the Auger electron through PCI were found to dominate the spectrum. Comparison with valence photoelectron spectrum of Kr via direct photoionization confirms the new assignment. Conjugate peaks were also found to be in accord with the quantum defect values obtained for the high Rydberg series Kr + 4 p −2 ( 1 S 0, 1 D 2 ) ml . Extension of the new assignments to photon energies below threshold may call for the revision of previous interpretations of resonance Auger processes.